Correlation of Ayurveda and Astrology on Health (AYUSHDHARA, 2022)
Ayurveda is huge and scientific system of healing that is practiced in India. It is appendages of Atharva veda so called as fifth Veda. Ayurveda improves our imbalance Dosha, Dhatwagni and Mahabhuta resulting into proper body constitution with the help of propitious diet and lifestyle. Astrology or Jyotish Vidya studies the influence of cosmic energy of planets on human. It was described in Rigveda & Ayurveda both. In Ayurveda there are many Ratna and Upratna which is being used in the form of Bhasma to cure diseases and that also represents the planetary system of universe and do control over cosmic rays. According to this our lives are strongly influenced by stars and planets. According to Veda, our Karma is directly related to position of planets and stars and thus astrology. In this paper we will see interconnecting relationship of planets and stars with Ayurveda especially with medicinal plants and mineral herbs and how could health be managed. In this article we will see the connection among plants, planets/stars, Dosha, Dhatu, Angavayava and Mahabhuta. And will also see the Sanchay and Prakopa kala of Dosha in the calendar of Ayurveda i.e., Samvatasar.